A generic coupling between internal states and activity leads to activation fronts and criticality in active systems - Hadrien-Matthieu Gascuel; Rahmani, Parisa; Bon, Richard; Peruani, Fernando (Physical review letters, 2024)
To understand the onset of collective motion, we investigate active systems where particles switch on and off their self-propulsion. We prove that even when the only possible transition is off\(→\)on, an active 2-state system behaves as an effective 3-state system that exhibits a sharp phase transition in 1D, and critical behavior in 2D, with scale-invariant activity avalanches. The obtained results show how criticality can naturally emerge in active systems, providing insight into the way collectives distribute, process, and respond to local environmental cues.